If it's not what You are looking for type in the equation solver your own equation and let us solve it.
0=(-5/7)x+4
We simplify the equation to the form, which is simple to understand
0=(-5/7)x+4
Simplifying:
0=(-0.714285714286)*x+4
Reorder the terms in parentheses
0=(-0.714285714286x)+4
Remove unnecessary parentheses
0=-0.714285714286x+4
We move all terms containing x to the left and all other terms to the right.
+ 0.714285714286x=+4-0
We simplify left and right side of the equation.
+ 0.714285714286x=+4
We divide both sides of the equation by 00.714285714286 to get x.
x=5.6
| 5x-2=-52 | | 3x-12y-4xy+x^2=0 | | 41s-11s-29s=26 | | .99n+98=1.98n | | 7-7x=-77 | | 9m-3=2m+46 | | 7w-12w+24=11 | | X-10=-6+2x | | 2d+19d+13d-32d=26 | | 6x-36=7 | | 6x-4=-76 | | -6x^2+9x+3=0 | | 8y-10=6y | | 5(2x-3)-x=x+1 | | 52u+9u+12u+4u-72u=75 | | 2x+8x=23.2 | | 1.07=2.3-1.2x | | -2+2x=20 | | 3n-8=2 | | x+2+8+x=20 | | 9x+2y=20 | | 61a-62a-31=-11 | | 2x+3=-1+3x | | 10x-6x-3x=2 | | -2x+3-4-4x=-10x+3+5x | | [3(7-5)-6]-[7-(2-6)]= | | 25y=15y^2 | | 6v+9=-5+3(v-6) | | 8t+3=15t+-11 | | 64v+9v-43v-28v=34 | | 8+log(8x)=29-2logx | | -8+4x=7x-41 |